Phase sequence in diisopropylammonium iodide: avoided ferroelectricity by the appearance of a reconstructed phase. Issue 3 (25th January 2017) - Piecha-Bisiorek, A.; Gągor, A.; Isakov, D.; Zieliński, P.; Gałązka, M.; Jakubas, R.
Abstract : Crystals of diisopropylammonium iodide are synthesized, grown and characterized. Abstract : Crystals of diisopropylammonium iodide are synthesized, grown and characterized. Two phases: P 21 / m ( Z = 1) and P 21 21 21 ( Z = 2) are observed. In contrast with analogous compounds no polar phase occurs, despite a critical-like electric behaviour. A phenomenological theory is proposed to describe the thermodynamics of the whole family of diisopropylammonium halides.